Explaining World Cultures to Students through Authentic Videos - Durdona Qambaraliyeva (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In an increasingly globalized world, fostering intercultural competence among students has become essential. This thesis explores the use of authentic videos as a powerful educational tool to introduce students to the diverse cultures of the world. Through exposure to real-life language, customs, traditions, and social behaviors captured in authentic video materials, students not only improve their language skills but also develop a deeper understanding of various cultural values. The study highlights effective strategies for integrating videos into the curriculum and presents practical recommendations for language and culture educators.